1997
DOI: 10.1080/016502597384767
|View full text |Cite
|
Sign up to set email alerts
|

Deductive Reasoning with Prose Passages: Effects of Age, Inference Form, Prior Knowledge, and Reading Skill

Abstract: This study applied knowledge about inference-making from the deductive reasoning literature to the drawing of speci c inferences from prose passages . It explored the effects of age, inference form, prior knowledge, and reading skill on inferential comprehension. In Experiment 1, fourth-grade, seventhgrade, and college students read three prose passages, each containing six inferential questions based on premises expressed in the passages. Premise information was either true, false, or neutral with regard to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…For all three age groups (including both college-educated and non-college educated adults in the oldest age group), the effects of form were first explored to see if the difference in difficulty found between indeterminate and determinate forms in the previous study (Franks, 1997) would also be found with this sample. As illustrated by Table 1, with determinate forms a logically necessary conclusion can be reached; with indeterminate forms, no conclusion can be reached.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…For all three age groups (including both college-educated and non-college educated adults in the oldest age group), the effects of form were first explored to see if the difference in difficulty found between indeterminate and determinate forms in the previous study (Franks, 1997) would also be found with this sample. As illustrated by Table 1, with determinate forms a logically necessary conclusion can be reached; with indeterminate forms, no conclusion can be reached.…”
Section: Resultsmentioning
confidence: 98%
“…MT, DA, and AC are often more difficult, even for adults Kodroff & Roberge, 1975;Taplin & Staudenmayer, 1973;Taplin, Staudenmayer, & Taddonio, 1974). However, in an earlier study using all these forms in prose passages (Franks, 1997), scores with DA and AC were significantly lower than scores with the other four forms, and scores on the other four forms were quite similar.…”
Section: Effects Of Inference Formmentioning
confidence: 84%
See 2 more Smart Citations
“…At relatively advanced levels of metalogical understanding, typically beginning about age 11, it becomes possible to recognize and evaluate the logical interconnections among propositions that are hypothetical or even false (Efklides, Demetriou, & Metallidou, 1994;Franks, 1996Franks, , 1997Markovits & Bouffard-Bouchard, 1992;Markovits & Nantel, 1989;Markovits & Vachon, 1989;Moshman & Franks, 1986). As a result, adolescents and adults are able to consider the potential interrelations of multiple possibilities and thus to formulate and test explicit theories (Inhelder & Piaget, 1958;Kuhn, Amsel, & O'Loughlin, 1988;Moshman, 1998, in press-a; Zimmerman, 2000).…”
Section: The Development Of Metalogical Understandingmentioning
confidence: 99%